Can explicit teaching of knowledge improve reading attainment? An evaluation of the Core Knowledge curriculum. (April 2017) - See, Beng Huat; Gorard, Stephen; Siddiqui, Nadia
Abstract : In England, as elsewhere, there is a tension in primary schools between imparting knowledge and teaching basic skills like literacy and numeracy. State‐mandated programmes are generally concerned with structure and skills. However, a number of ministers and advisers across administrations have sought to expand the explicit teaching of world knowledge (culture, geography and science) as advocated by E. D. Hirsch in the Core Knowledge curriculum. This paper describes an independent evaluation of an adaptation of that approach, called the 'Word and World Reading' programme as used with children aged 7 to 9 in England, to assess its impact on wider literacy. Nine primary schools were randomised to receive the intervention from the start and another eight a year later. The outcomes, assessed by the Progress in English test in literacy after one year, showed no discernible effect overall ('effect' size −0.03), and a small improvement for those eligible for free school meals (+0.06). There was no school dropout, but the missing data for around 18% of 1628 pupils means the results must be treated with some caution. Observations suggest that the lack of clear benefits could be due to the poor quality of implementation in some schools or classes. Perhaps teachers as professionals do not respond well to prescriptive curricula. It is also possible that factual knowledge does not translate directly to improved literacy skills, at least not within one year. Teaching children facts alone in this way cannot be justified solely in terms of improved literacy. Even the scheme on which this intervention was based stressed the need for pupils to learn how to handle facts as well as to learn the facts themselves.